Impact of Machine Learning Applications For Price Prediction Of Onion In India - Sayed Mannan Ahmad; Ankush Kumar Gaur; Anil Kumar (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Conceptual India is one of the second-biggest maker of onion on the planet. Onion is the most extravagant wellspring of nutrients and cell reinforcements. Furthermore, it contains malignant growth battling mixes, assists with keeping up heart more advantageous and lifts the bone thickness, additionally controls the glucose. Natural just as Climate changes sway on the rural economy of any nation. The creation of onion typically relies upon factors like science, atmosphere, economy, and topography, these elements impact on agriculture. It is been recorded that significant expense chance in the horticulture part constantly bound ranchers to endeavor suicide. The value figures are helpful for homesteads, policymakers, and agribusiness ventures. Utilizing time arrangement information in horticulture, nonstop endeavors are made by the analysts to foresee the costs utilizing different straight and nonlinear anticipating models. These days, Artificial knowledge/Machine learning models are utilized as traditional measurable models in the gauging exercise. Utilizing AI strategies in this way, utilizing authentic cost and information factors. Henceforth this exploration will assume a significant job to anticipate the cost of onion. Just as help to agriculturists to turn out to be financially well and has a more advantageous existence.